Hubungan Tingkat Pengetahuan Tentang Dismenorea dengan Sikap Menghadapi Dismenorea di Sekolah Menengah Pertama Negeri 4 Sukoharjo The relationship between the level of knowledge of Dysmenorrhoea with the caring behavior of Junior High School student 4 Suk - Wulandari, Suci; - Poltekkes Bhakti Mulia Sukoharjo, Sri Setiyo Ningrum (IJMS - Indonesian Journal on Medical Science, 2018)
Abstract: Dysmenorrhoea is abdominal pain that comes from the uterine cramping and occurs during menstruation can interfere with daily activities. Behavior that indicated young women depending on their knowledge. Knowledge of dysmenorrhoea very influential towards the attitude in addressing the dysmenorrhoea. The effort faced dysmenorrhoea conducted by students are medically and non-medically. The purpose of this research is to know the relation between the level of knowledge of dysmenorrhoea with attitude faced the first middle school in the disminorea Junior High School student affairs 4 Sukoharjo. This research method using analytic survey research with cross sectional approach. The subject is a Junior High School student affairs 4 Sukoharjo class VIII as much as 99 people by using purposive sampling technique. Data analysis techniques using the test statistic Chi Square. The results showed that knowledge about the disminorea retrieved value X2 countdown (51.606) > X2 table (22.368) and the attitude of the retrieved value X2 countdown (58.727) > X2 tables (23.685), so that knowledge and attitudinal values obtained p value (0.000 < 0.05). There is a significant relationship between the level of knowledge about disminorea against the attitude of facing disminorea.Keywords: Knowledge, Attitude, DysmenorrhoeaÂ Abstrak: Dismenorea adalah nyeri perut yang berasal dari kram rahim dan terjadi selama menstruasi yang dapat mengganggu aktivitas sehari-hari. Perilaku yang ditunjukkan remaja putri tergantung pengetahuan yang dimiliki. Pengetahuan tentang dismenorea sangat berpengaruh terhadap sikap dalam mengatasi dismenorea. Upaya menghadapi dismenorea yang dilakukan oleh siswi adalah secara medis dan non medis. Tujuan penelitian ini Untuk mengetahuiÂ hubungan antara tingkat pengetahuan tentang dismenorea dengan sikap menghadapi disminorea di Sekolah Menengah Pertama (SMP) Negeri 4 Sukoharjo. Metode penelitian ini menggunakan penelitian survey analitik dengan pendekatan cross sectional. Subjek penelitian adalah siswi SMP Negeri 4 Sukoharjo Kelas VIII sebanyak 99 orang dengan menggunakan teknik purposive sampling. Teknik analisis data menggunakan uji statistic Chi Square. Hasil penelitian menunjukkan bahwa pengetahuan tentang disminorea diperoleh nilai X2 hitung (51,606) > X2 tabel (22,368) dan sikap diperoleh nilai X2 hitung (58,727) > X2 tabel (23,685), sehingga pengetahuan dan sikap didapatkan nilai p value (0,000 < 0,05). Ada hubungan signifikan antara tingkat pengetahuan tentang disminorea terhadap sikap menghadapi disminorea.Kata Kunci: Pengetahuan, Sikap, Dismenorea